The impact of capacity and location of multidistributed generator integrated in the distribution system on electrical line losses, reliability, and interruption cost - Chiradeja, Pathomthat; Ngaopitakkul, Atthapol (My University, 2015)
The primary purpose of this article is to study the impact of distributed generator (DG) integrated into the distribution system in terms of electrical line losses, reliability and interruption cost. The single- and multi-distributed generators (DG) under this study are connected to a 22 kV distribution system of the Provincial Electricity Authority (PEA) that is a part of Thailand's distribution system. Geographic information systems data, including the lengths of the distribution line and the load locations that are key parameters of PEA, are simulated using digital simulation and electrical network calculation program (DIgSILENT). In addition, the capacity and location of DG installed into the distribution system are considered. The system average interruption frequency index (SAIFI), the system average interruption duration index (SAIDI) and the interruption cost are assessed as reliability indices by comparing the SAIFI, SAIDI, and interruption cost of the base case (without DG) and the cases of single- and multi-DGs connected to the distribution system. Moreover, the electrical line loss is considered in terms of active power line loss, which is also compared with the base case. The results can be summarized by focusing on the location of DG, the capacity of DG, the number of DG, the size of the load, and the distance to the load, which are factors capable of impacting the electrical line loss, SAIFI, SAIDI, and interruption cost.
Keywords: distributed generation; distribution system; electrical line loss; reliability